Mechanisms of otoconia and otolith development. Issue 3 (18th October 2014) - Lundberg, Yunxia Wang; Xu, Yinfang; Thiessen, Kevin D.; Kramer, Kenneth L.; Trainor, Paul; Johnson, Randy
<x xml:space="preserve">Abstract</x> Background: Otoconia are bio‐crystals that couple mechanic forces to the sensory hair cells in the utricle and saccule, a process essential for us to sense linear acceleration and gravity for the purpose of maintaining bodily balance. In fish, structurally similar bio‐crystals called otoliths mediate both balance and hearing. Otoconia abnormalities are common and can cause vertigo and imbalance in humans. However, the molecular etiology of these illnesses is unknown, as investigators have only begun to identify genes important for otoconia formation in recent years. Results: To date, in‐depth studies of selected mouse otoconial proteins have been performed, and about 75 zebrafish genes have been identified to be important for otolith development. Conclusions: This review will summarize recent findings as well as compare otoconia and otolith development. It will provide an updated brief review of otoconial proteins along with an overview of the cells and cellular processes involved. While continued efforts are needed to thoroughly understand the molecular mechanisms underlying otoconia and otolith development, it is clear that the process involves a series of temporally and spatially specific events that are tightly coordinated by numerous proteins. Such knowledge will serve as the foundation to uncover the molecular causes of human otoconia‐related disorders. Developmental Dynamics 244:239–253, 2015. © 2014 Wiley Periodicals, Inc.